Evaluating Mandatory Corporate Social Responsibility Disclosure Policies and Sustainability Development Goals Achievement in Indonesia - Windari, Ratna Artha; Dewi, Yetty Komalasari (Yustisia, 2024)
The enactment of the 2007 Company Law confirms Indonesia’s requirement for mandatory disclosure of Corporate Social Responsibility (CSR). However, there has not been any research specifically examining CSR activities from the report disclosed. Only a few studies have examined the mandatory disclosure of CSR for companies whose core business does not directly include natural resources but whose activities significantly impact the environment. Therefore, this research aimed to evaluate and analyse the mandatory disclosure of CSR through company annual  reports,  taking  a  sample  of  listed  textile  businesses in Indonesia and the correlation with the achievement of Sustainability Development Goals (SDGs). The findings showed that  the  mandatory  disclosure  regulations  in  2007  Company Law and Financial Service Authority Regulation Number 51/ POJK.03/2017 failed to improve optimal CSR implementation by textile companies in Indonesia. Various textile companies focused more on community development while paying little attention to environmental concerns. Additionally, detailed and explicit provisions were lacking in achieving the SDGs target. Reformulation of CSR disclosure policies was necessary to regulate reporting procedures, content, and criteria for environmental aspects of the programs in annual reports while correlating with the targets of the 2030 SDGs policy.